Field Approach on the Effectiveness of Hydraulic Flocculator Followed By Sedimentation and Rapid Sand Filter - Pyakurel, Hari Ram; Khatri, Nam Raj; Lekhak, Basant (Himalayan Journal of Applied Science and Engineering, 2024)
This research investigates the effectiveness of a hydraulic flocculator at the Kalanki Groundwater Treatment Project-Sipradi in Kalanki-Kathmandu. Hydraulic flocculation is a cost-effective alternative to mechanical flocculation, particularly beneficial for developing nations. The study involved determining the optimal Poly Aluminium Chloride (PACl) dosage through Jar Testing and assessing the flocculator’s efficiency in the field with this dose. The research also analyzed other treatment units under various PACl doses to evaluate the Water Treatment Plant’s operational conditions and the required PACl dose for efficient turbidity removal. The system included components like a deep well source, V-Notch weir tank, hydraulic flocculator, sedimentation tank, rapid sand filter (RSF), chlorinator, and clear water reservoir, with a 16-minute flocculator detention time. Baffle walls were strategically positioned at various intervals on-site. The study revealed that while sedimentation with coagulation achieved peak efficiency at a PACl dose of 80mg/l, it was less efficient than a 16-minute jar detention, likely due to sedimentation tank short-circuiting. Increasing the PACl dose from 20 mg/l to 80 mg/l improved overall unit efficiency, indicating the need for more mixing energy in the existing flocculator length for optimal results. The filter unit’s efficiency remained consistent, whether with or without coagulation, at 57.69% and 54.10%, respectively. These results emphasize the importance of further investigation to enhance water treatment processes and coagulant dosages for improved effectiveness in this critical field.